Optimization Of Data Mining In Predicting Tourist Visits At The Deli Serdang Museum - Wahyuni, Sri; Nasution, Afri Deliansyah; Hermansyah, Hermansyah (International Conference on Sciences Development and Technology, 2023)
The PKM Programme aims to increase tourism and promotional media even in the midst of the Covid-19 pandemic by using information technology, particularly data mining, to help Deli Museum employees forecast the number of visitors to the museum. The information gathered from this process can then be utilised to inform policy decisions. The information that is produced can be innovatively and creatively used to implement commercial strategies that will boost public interest in and passion for visiting the Deli Serdang museum. As the first step in putting this PKM programme activity into practice, the team in the present Community Service programme teaches students how to retrieve and gather data at the Deli Serdang Museum in addition to teaching them how to use technology, particularly the Data Mining application. The Deli Serdang Youth, Sports, Culture and Tourism Department is the program's target audience, with a focus on museum staff in particular. The team evaluated the participants' ability to accept and assimilate the material by giving them tests at the end of the PKM series. This allowed the team to determine how well the participants understood the material.